Cruise Ship Astronomy and Astrophotography - Redfern, Gregory I. (The Patrick Moore Practical Astronomy Series,, 2018)
Enrich your next sea vacation with this fun how-to guide to observing and doing astrophotography on water. Collecting together the author's five decades of astrophotography and teaching experience, this book shares all the practical information you will need to start on your own astronomy adventure. Part I is full of practical advice on what to pack, the best ways to enjoy the night sky from your cruise ship observatory, specific astronomical objects and events to look out for, and myriad other useful tips. Part II gives you a crash course on astrophotography at sea, teaching you the nitty-gritty details of taking pictures of the night sky. Proof that it can be done is provided by the many amazing color astrophotographs taken by the author while following the steps laid out in this book.